Gastric Necrosis After Binge Eating in Bulimia: Recovery From Eating Disorder After Total Gastrectomy - Achamrah, Najate; Grigioni, Sébastien; Coëffier, Moïse; Ainseba, Nadjib; Déchelotte, Pierre (Frontiers in Psychiatry, 2020)
Background: Gastric necrosis following acute gastric dilatation is rare but more common in females with eating disorders, such as anorexia nervosa or bulimia, during which patients often alternate restriction and binge eating behaviours. Case presentation: A 37-year old female patient with a history of 15 years of bulimia nervosa was admitted to the emergency department 24 hours after binge eating. Abdominal Computed Tomography imaging showed major gastric distension reaching the pelvis and compressing the digestive organs. Total gastrectomy was required because of gastric necrosis. The patient reported significant reduction in bulimic symptoms after gastrectomy. Conclusion: We discuss here the possible mechanisms underlying this recovery, including changes in gut-derived factors that could mediate eating behaviour changes.